Regulating Thermal Performance and Emission Characteristics of a Large-Bore Two-Stroke Marine Diesel Engine Fueled with Methyl Decanoate/Diethyl Ether Blends: A Full-Cylinder CFD Study - Shiye Wang; Peiyuan Wang; Jianghua Sui; Haopeng Chen (Journal of Marine Science and Engineering, 2026)
A full-cylinder CFD model was developed to investigate methyl decanoate (MD)/diethyl ether (DEE) blends in a MAN B&W 7S80ME-C9 two-stroke diesel engine at 75% load. The model retained the multi-injector configuration, asymmetric spray development, scavenging and exhaust processes, and in-cylinder combustion of the 800 mm-bore engine. Four equal-energy cases, MD100, MD95, MD90, and MD85, were considered, with DEE energy fractions of 0%, 5%, 10%, and 15%. DEE blending regulated spray evaporation, mixture formation, heat-release phasing, and expansion work conversion. Increasing the DEE fraction enhanced evaporation and gas-phase mixing, but stronger mixing did not necessarily improve thermal performance. The peak-pressure trend differed from the net indicated work trend, indicating that work output was governed more by pressure evolution during expansion than by peak pressure alone. MD90 maintained stronger post-injection heat release and a more favorable equivalence-ratio distribution, thereby achieving the highest net indicated work, 6.70% higher than MD100. Although MD90 showed a high mean temperature, it produced the lowest NO and NO2 emissions because NOX formation depended on the local coupling of temperature, oxygen availability, equivalence ratio, and residence time. The CO2 level was lowest for MD100 among the four fuel cases. At 75% load, MD90 provided a favorable balance among heat-release phasing, net indicated work, and emission control across the four investigated fuel cases.